The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10120-006-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous gastric cancers after endoscopic resection: how effective is annual endoscopic surveillance?

Abstract: In order to detect MGC at a stage early enough for a curative repeat ER, an annual endoscopic surveillance program is both practical and effective for post-ER patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
185
5
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(219 citation statements)
references
References 27 publications
(27 reference statements)
18
185
5
3
Order By: Relevance
“…However, almost 20 % of the secondary lesions were also found more than 3 years after endoscopic resection, suggesting that long-term follow-up also cannot be ignored. In a previous study of metachronous gastric cancer after endoscopic resection, the overall incidence was reported to be 8.2 % during an average of 3.1 years of follow-up, and the cumulative 3-year incidence of metachronous gastric cancer was 5.9 % [19]. Another study reported that metachronous gastric cancers had an overall incidence of 14 % during a median of 57 months of follow-up [12], and yet another study showed the incidence of synchronous and metachronous multiple gastric cancers after endoscopic resection to be 14.5 and 8.5 %, respectively [15].…”
Section: Discussionmentioning
confidence: 95%
“…However, almost 20 % of the secondary lesions were also found more than 3 years after endoscopic resection, suggesting that long-term follow-up also cannot be ignored. In a previous study of metachronous gastric cancer after endoscopic resection, the overall incidence was reported to be 8.2 % during an average of 3.1 years of follow-up, and the cumulative 3-year incidence of metachronous gastric cancer was 5.9 % [19]. Another study reported that metachronous gastric cancers had an overall incidence of 14 % during a median of 57 months of follow-up [12], and yet another study showed the incidence of synchronous and metachronous multiple gastric cancers after endoscopic resection to be 14.5 and 8.5 %, respectively [15].…”
Section: Discussionmentioning
confidence: 95%
“…Since the proportion of patients with a different diagnosis in the response of matched pairs was 58 %, the sample size was set to 26 cancerous lesions. The frequency of synchronous or metachronous multiple gastric cancers in patients with previous gastric cancers was reported as 3-5 per 100 patient-years [18][19][20]. Moreover, it was reported that the frequency of synchronous or metachronous gastric cancers was 7.7 % in patients with esophageal cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of metachronous gastric cancer (MGC), owing to the preservation of the entire stomach after endoscopic resection, remains a possibility [8][9][10]. A previous multicenter prospective randomized study performed in Japan showed that eradication of Helicobacter pylori reduced the incidence of MGC after endoscopic resection for early gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%